Aplikasi Remote Sensing dan Geographic Information System untuk Perencanaan Penggunaan Lahan Pertanian Berbasis Agroekosistem di Kota Denpasar - REHMAMANA, RIAN; LANYA, INDAYATI; DIBIA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.9, No.1, Januari 2020, 2020)
Remote Sensing and Geographic Information System Application for Agroecosystem Based Agricultural Land Planning in Denpasar City This study aims to determine the level of potential agroecosystem land suitability, compile databases, build information systems and create maps of land use planning for food crops and horticulture based on remote sensing and Geographic Information System (GIS). This research took place from September 2018 - December 2018 using an exploratory method which included analysis of satellite imagery, field surveys, analysis of field data and laboratory data, land suitability classification, mapping of land suitability classes, compiling data bases, building information systems, commodity zoning, planning land use, and mapping of land use planning. Potential land suitability classes for irrigated rice fields are generally very suitable in all of Denpasar City (41 subak) but additional fertilizer is needed, especially N. Potential land suitability classes for horticultural (vegetable and fruit) commodities are classified as appropriate (S2) through drainage improvements and fertilization. Climate factors are generally very suitable (S1) for food crops, and suitable (S2) for horticulture plants. The train factor is generally classified as very suitable (S1) in food crops and horticulture unless the drainage factor is relatively slow and nutrient availability is classified as moderate.